Post-stack diffraction imaging in vertical transverse isotropy media using non-hyperbolic moveout approximations - Khoshnavaz, M.; Bóna, A.; Urosevic, Milovan (Wiley-Blackwell, 2017)
Diffractions carry valuable information about local discontinuities and small-scale objects in the subsurface. They are still not commonly used in the process of geological interpretation. Many diffraction imaging techniques have been developed and applied for isotropic media, whereas relatively few techniques have been developed for anisotropic media. Ignoring anisotropy can result in low-resolution images with wrongly positioned or spurious diffractors. In this article, we suggest taking anisotropy into account in two-dimensional post-stack domain by considering P-wave non-hyperbolic diffraction traveltime approximations for vertical transverse isotropy media, previously developed for reflection seismology. The accuracy of the final images is directly connected to the accuracy of the diffraction traveltime approximations. We quantified the accuracy of six different approximations, including hyperbolic moveout approximation, by the application of a post-stack diffraction imaging technique on two-dimensional synthetic data examples.